-10(x-7)-7(k-10)=

Simple and best practice solution for -10(x-7)-7(k-10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(x-7)-7(k-10)= equation:


Simplifying
-10(x + -7) + -7(k + -10) = 0

Reorder the terms:
-10(-7 + x) + -7(k + -10) = 0
(-7 * -10 + x * -10) + -7(k + -10) = 0
(70 + -10x) + -7(k + -10) = 0

Reorder the terms:
70 + -10x + -7(-10 + k) = 0
70 + -10x + (-10 * -7 + k * -7) = 0
70 + -10x + (70 + -7k) = 0

Reorder the terms:
70 + 70 + -7k + -10x = 0

Combine like terms: 70 + 70 = 140
140 + -7k + -10x = 0

Solving
140 + -7k + -10x = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-140' to each side of the equation.
140 + -7k + -140 + -10x = 0 + -140

Reorder the terms:
140 + -140 + -7k + -10x = 0 + -140

Combine like terms: 140 + -140 = 0
0 + -7k + -10x = 0 + -140
-7k + -10x = 0 + -140

Combine like terms: 0 + -140 = -140
-7k + -10x = -140

Add '10x' to each side of the equation.
-7k + -10x + 10x = -140 + 10x

Combine like terms: -10x + 10x = 0
-7k + 0 = -140 + 10x
-7k = -140 + 10x

Divide each side by '-7'.
k = 20 + -1.428571429x

Simplifying
k = 20 + -1.428571429x

See similar equations:

| 7(-1m-1)=49 | | 4(5t+10)=-60 | | 6(4m-1)=162 | | -10(x-7)-3(k-10)= | | 75/8*-7=x | | 3(5-7t)=-216 | | 6(6+7t)=246 | | 6(5d+10)=-180 | | 5(1d-7)=-95 | | 75/8*18=x | | 75/8*18 | | 4(3+a)=24 | | 3(-5d+10)=30 | | 4(-4+7k)=-128 | | 4(3t-3)=-24 | | 4(1+7n)=144 | | 5(3+3k)=60 | | 6(-10+x)=-90 | | 5(-6n-4)=-350 | | 2(5b+8)=-34 | | 5(5-7w)=25 | | 2(7a+3)=76 | | 4(1w+1)=44 | | 4+2x=7+3x | | 75/8*7=x | | 5(-4-2d)=-80 | | 4(2+6b)=104 | | 5(-1-5n)=-80 | | 2(8-4d)=-48 | | 5(3t+9)=150 | | 7(1-7w)=-434 | | .2(50)+.8x=.4(50+x) |

Equations solver categories